The Need for Simulated Patient Method Implementation in Pharmaceutical Education in Poland - Cerbin-Koczorowska, Magdalena; Przymuszała, Piotr; Nowaczyk, Magdalena Waszyk-; Plewka, Beata; Marciniak, Ryszard (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Changing societal expectations towards pharmacy graduates and increased focus on communication skills, interprofessional collaboration and pharmaceutical care in their curricula, point out necessity of using new educational techniques to introduce pharmacy students to more practical elements of their future profession. Purposes: The aim of presented study was to introduce and discuss the simulated patient method (SP-method) and indicate potential areas of its implementation into pharmacy curriculum, in terms of qualifications of graduates, on the example of Polish legislation. Methodology: PubMed and Google Scholar databases were searched to identify full text English language articles on application of the SP-method in educational scenarios, with particular emphasis on pharmaceutical education. Additionally, the new Ordinance of the Polish Minister of Science and Higher Education, defining educational standards for undergraduate pharmaceutical education, was analysed in search of learning outcomes that could be achieved and verified using the SP-method. Given that the Bloom’s cognitive domain can be supported with cheaper educational methods, presented study focused mainly on practical skills. Results: The key findings suggest that the SP-method allows to accomplish many skill-based learning outcomes defined in the undergraduate pharmaceutical curriculum. Potential areas of its implementation include: enhancing communication skills, patient counselling skills, patient education and pharmaceutical care, teamwork and interprofessional collaboration. Conclusion: Pharmacy students, similarly to their colleagues studying medicine or nursing, should be given opportunities to learn using the SP-method.
Keywords: Simulated patients; Pharmacy students; Pharmaceutical education; Pharmaceutical curriculum; Practical skills